Mapping of individual dislocations with dark‐field X‐ray microscopy. Issue 1 (1st February 2019) - Jakobsen, A. C.; Simons, H.; Ludwig, W.; Yildirim, C.; Leemreize, H.; Porz, L.; Detlefs, C.; Poulsen, H. F.
Abstract : An X‐ray microscopy approach for mapping deeply embedded dislocations with a resolution of currently 200 nm is presented. The technique involves scanning an aperture in the back focal plane, which allows the strain fields around dislocations to be visualised with a strain resolution better than 10 −4 . Abstract : This article presents an X‐ray microscopy approach for mapping deeply embedded dislocations in three dimensions using a monochromatic beam with a low divergence. Magnified images are acquired by inserting an X‐ray objective lens in the diffracted beam. The strain fields close to the core of dislocations give rise to scattering at angles where weak beam conditions are obtained. Analytical expressions are derived for the image contrast. While the use of the objective implies an integration over two directions in reciprocal space, scanning an aperture in the back focal plane of the microscope allows a reciprocal‐space resolution of Δ Q / Q < 5 × 10 −5 in all directions, ultimately enabling high‐precision mapping of lattice strain and tilt. The approach is demonstrated on three types of samples: a multi‐scale study of a large diamond crystal in transmission, magnified section topography on a 140 µm‐thick SrTiO3 sample and a reflection study of misfit dislocations in a 120 nm‐thick BiFeO3 film epitaxially grown on a thick substrate. With optimal contrast, the half‐widths at half‐maximum of the dislocation lines are 200 nm.